IN-DEPTH ANALYSIS OF THE HISTORICAL TERMS RELATED TO THE COMMON LAW “TRUST” - Irina GVELESIANI (Challenges of the Knowledge Society, 2016)
“It is at least possible that the trust will in the 21st century join those other English inventions, such as football and the steam engine, which have swept the world”1.The given optimistic definition of common law “trust” enables us to regard it as a unique legal instrument. However, its origin is the source of numerous debates of the scholars of the world. Scientific literature presents three theories concerning the origin of the “trust”: Roman, Germanic and Islamic. Until the nineteenth century, it had been believed, that the trust had been modeled on the Roman legal institution “fideicommissum”. However, by the nineteenth century, the given theory was replaced by the new assumption, which proposed, that the Salic “Salmannus” had been a predecessor of the “trust”. The debates about the origin of this institution were fueled by the fact, that the English “use” (an initial form of the trust), the Roman “fideicommissum” and the Salic “Salmannus” had the same cause of emergence: they emerged as a “result of positive-law deficiencies and restrictions concerning the ownership and devolution of property”2 during those times, when the land was the principle form of wealth. The given paper presents an attempt to highlight the existed theories about the origin of the “trust” and make new conclusions on the basis of in-depth terminological analysis. Synchronic and diachronic approaches initiate insights into the juridical and lingual developments.